Bilateral Cerebral Venous Thrombosis with a Rare Presentation in a COVID-19 Patient: A Case Report - Ahrari, Iman; Saffarian, Arash; Rakhsha, Abbas; Ghavipisheh, Mahsa; Gholami, Mohamad Reza (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Since the COVID-19 pandemic started, millions of peoples are involved. The presentation of the disease varies from mild respiratory symptoms and multiple organ failure to coma and death. Neurological symptoms such as headache or seizure are also coincident with COVID-19. Thromboembolic events increase in COVID-19 patients due to hypercoagulability and inflammation, particularly in severely ill patients. Thrombosis may cause venous thrombosis, pulmonary embolism, or cerebral sinus venous thrombosis (CSVT). Cerebral sinus venous thrombosis is a rare phenomenon that is usually found in critically ill patients with bad prognoses. In the present case report, we present a 40-year-old man with COVID-19 confirmed by real-time polymerase chain reaction (RT-PCR) who was admitted due to acute bilateral visual loss due to bilateral transverse sinus thrombosis. Pseudotumor cerebri disease was confirmed through high lumbar puncture. Early surgical intervention (optic nerve fenestration) was performed and, fortunately, his visual acuity improved. Cerebral sinus venous thrombosis is a rare incident in COVID-19 patients, but due to irreversible complications, an early diagnosis is fundamental. In any neurologic change in COVID-19 patients, CSVT must be considered. Also, prophylactic thrombolytic therapy should be kept in mind as the patient is admitted.
Keywords: SARS-COV-19; CSVT; thrombosis; pseudotumor cerebri; venous thrombotic event; visual loss